Arena 13 - Delaney, Joseph (UK Red Fox, 2015)
The city of Midgard is terrorised by Hob, a terrifying, evil creature who tortures at will and has the rulers of the city completely under his control. The thirteen fighting arenas in the citiy are forever full with punters eager to make their fortune betting on the fights that take place there. The most popular - and the most terrifying of these - is the thirteen arena, the arena where the Trig fighters battle. Sixteen-year-old Leif is determined to train as a Trig fighter and gets himself apprenticed to Tyron, the greatest of all trainers. But little does his new trainer or the other apprentices know, Leif has a personal battle to fight. He's going to avenge the death of his father by killing Hob himself ...
Keywords: Monsters -- Revenge -- Teenage boys